Efikasi Injeksi Lidocain pada Myofascial Pain - Rr Pruelinnisa Inori Hapkido; Zamroni Zamroni (Inovasi Kesehatan Global, 2025)
Background: Indonesia, as an agrarian country, has a large workforce engaged in physically demanding activities that increase the risk of myofascial pain. The prevalence of myofascial pain syndrome (MPS) in the upper trapezius muscle in Indonesia reaches 40% annually, with a higher rate in women. This condition often causes complaints in the neck, shoulders, and lower back, leading to a decline in quality of life. Various management strategies exist, but many are less effective in the long term and carry potential side effects. Lidocaine, as a local anesthetic, offers an alternative therapy due to its simple procedure, affordable cost, rapid effect, and good safety profile; therefore, its effectiveness in managing myofascial pain needs to be evaluated. Methods: This study was an observational research with a prospective cohort design conducted at PKU Muhammadiyah Gamping Hospital. Patients with myofascial pain who received lidocaine injections were followed for 4 weeks, and pain intensity was measured using the Numeric Rating Scale (NRS) to assess the relationship between lidocaine administration and pain reduction. Results: The study showed that lidocaine injection was effective in significantly reducing myofascial pain. The Wilcoxon Signed Rank Test produced negative Z values with p = 0.000 (<0.05) for all comparisons from pretest to the fourth week. The Friedman test also indicated significant differences between weeks (χ² = 9.731; p = 0.021), with optimal pain reduction observed in the second week. Although lidocaine provided significant analgesic effects, its effectiveness tended to decrease in subsequent weeks, indicating a short-term effect that should be combined with other interventions for sustained outcomes. Conclusion: Lidocaine injection proved effective in reducing pain among patients with myofascial pain syndrome, with the most optimal reduction occurring in the second week after therapy. The dominant factors influencing the outcomes were the relatively short duration of lidocaine’s action and individual variability in response. This implies that lidocaine can be used as an effective initial therapy, but should be combined with other interventions such as physiotherapy or activity modification to achieve more stable and sustainable pain management.